THE IMPORTANCE OF A PARTICIPATORY APPROACH IN VILLAGE DEVELOPMENT IN THE VILLAGE OF TANJUNG MEDAN LABUHAN BATU SELATAN - Salsabila Balqis Siregar; Julia Ivanna (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The participatory approach in village development prioritizes the active role of the community as the main actors, with full involvement in every stage of development, from planning to evaluation. This concept is based on the capabilities and self-reliance of the community, as well as continuous learning built from their experiences, ensuring that village development aligns more closely with the community's capabilities and progress. This study employs a descriptive method with a qualitative approach to understand community participation in Tanjung Medan Village, South Labuhan Batu Regency. Data were collected through direct observation, surveys, and interviews with the village head and the community. The results show that although the community participates in gotong royong activities and program evaluations, there is dissatisfaction with the village government's transparency, particularly regarding budget reporting. Improvements in the evaluation and monitoring phases are needed to enhance the effectiveness of the participatory approach